Dynamic balance is impaired after a match in young elite soccer players - Pau, M.; Mereu, F.; Melis, M.; Leban, B.; Corona, F.; Ibba, G. (Physical Therapy in Sport, 2016)
Purpose: The aim of this study is to assess the effect of actual match effort on dynamic balance abilities in young elite soccer players.